Family functioning and suicidal ideation in college students: a moderated mediation model of depression and acceptance - Biao Peng; Ningning Hu; Li Guan; Chao Chen; Zhu Chen; Huiying Yu; Huiying Yu (Frontiers Media S.A., 2023)
ObjectiveTo explore the mediating role of depression in the relationship between family functioning and suicidal ideation (SI) in college students, and to explore whether acceptance (It is one of the core components of psychological flexibility) plays a moderating role in this mediating model.MethodsIn a cross-sectional study, questionnaires were distributed to college students during November and December 2022. The sample of Chinese college students (n = 592, 43.07% male, 56.93% female, mean age 19.40 years, SD = 1.24 years) completed the Family Adaptability and Cohesion Evaluation Scale (FACES III), the Center for Epidemiological Depression Scale (CES-D), the Positive and Negative Suicide Ideation Inventory (PANSI), and the Acceptance and Action Questionnaire-Second Edition (AAQ II). SPSS 25.0 for Windows and PROCESS 2.15 macros were used for data analysis.ResultsThere was a significant negative correlation between family functioning and SI, and depression played a mediating role in this relationship. Acceptance moderated the indirect effects of depression and SI in college students. In college students with a lower acceptance level (i.e., higher experiential avoidance level), depression had more influence on SI, while the influence of depression on SI was less in college students with a higher acceptance level (i.e., lower experiential avoidance level). Family functioning indirectly influenced SI through the moderation of acceptance.ConclusionMental health educators in colleges and universities should pay more attention to identifying and relieving depression in college students, thereby dealing with suicide risk more effectively. At the same time, college students should be discouraged from excessive use of experiential avoidance strategies, and instead taught to master effective emotional regulation strategies such as mindfulness, distress tolerance, and radical acceptance skills to improve their acceptance level and alleviate the influence of depression on SI.